2014
DOI: 10.2217/nnm.13.136
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biophysical Properties of Tenofovir-Loaded, Thiolated and Nonthiolated Chitosan Nanoparticles Intended for HIV Prevention

Abstract: Aim This study is designed to test the hypothesis that tenofovir-loaded (an anti-HIV microbicide) chitosan–thioglycolic acid-conjugated (CS–TGA) nanoparticles (NPs) exhibit superior biophysical properties for mucoadhesion compared with those of native CS NPs. Materials & methods The NPs are prepared by ionotropic gelation. The particle mean diameter, encapsulation efficiency and release profile are analyzed by dynamic light scattering and UV spectroscopy, respectively. The cytotoxicity, cellular uptake and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 69 publications
(76 reference statements)
0
27
0
Order By: Relevance
“…Cytotoxicity studies conducted on glycol CS hydrogels with progesterone revealed no significant influence on the viability of human vaginal epithelial cells [15]. It has also been reported that tenofovir-loaded, thiolated and nonthiolated CS nanoparticles had no cytotoxic effect on vaginal epithelial cells [61]. In contrast, Depani et al, found that CS/glycerol phosphate gels exhibit dose-dependent cytotoxicity on mouse fibroblasts L-929 cells [29].…”
Section: K0mentioning
confidence: 97%
See 1 more Smart Citation
“…Cytotoxicity studies conducted on glycol CS hydrogels with progesterone revealed no significant influence on the viability of human vaginal epithelial cells [15]. It has also been reported that tenofovir-loaded, thiolated and nonthiolated CS nanoparticles had no cytotoxic effect on vaginal epithelial cells [61]. In contrast, Depani et al, found that CS/glycerol phosphate gels exhibit dose-dependent cytotoxicity on mouse fibroblasts L-929 cells [29].…”
Section: K0mentioning
confidence: 97%
“…As a result, CS has been widely used in biomedical applications (e.g., for the development of scaffolds for skin transplantation or wound dressings) and as diet supplement. Despite the fact that CS is widely used as a drug delivery carrier and has been extensively studied for topical [59,60] and vaginal [61] drug delivery, its safety profile has still not been fully evaluated. The polymer biocompatibility can be influenced by the purity and the source of the material used, the particle size, degree of deacetylation, concentration, dosage form and the route of administration [58].…”
Section: In Vitro Cytotoxicity Evaluationmentioning
confidence: 99%
“…However, TDF has considerable water solubility (13.4 mg/ml at 25°C), and it is well known that hydrophilic drugs are not easy to encapsulate into nanoparticles. There have been few attempts to encapsulate TFV or TDF in PLGA nanoparticles (27,28). None of these investigations were able to achieve greater than 10% encapsulation of TFV or TDF in the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to partially substitute water by non-solvents, such as ethanol, optimized association efficiencies have been usually less than around 25%, thus resulting in poor drug loading, usually no more than up to 2% [100][101].…”
Section: Prevention Of Hiv Transmissionmentioning
confidence: 99%